FinTech: enhancers and replacers - Cumps, Bjorn (Henry Stewart Talks, 2018)
This case study explores two ways in which FinTech is transforming the financial services industry. The two contrasting examples demonstrate that not all FinTech developments are fundamentally disruptive, and that as a result the financial services industry is not being as dramatically changed by FinTech as you might imagine.